E-119 Surpass streamline flow diverter use in treating cervical carotid pseudoaneurysms: a case series. (4th August 2020) - Achey, R; Sheikhi, L; Patterson, T; Toth, G; Zobenica Moore, N; Bain, M
Abstract : Introduction: Flow diverter stents have revolutionized endovascular treatment for cerebral aneurysms not amenable to coil embolization. Originally, the Pipeline embolization device (PED) emerged as a novel system for treating large/giant, or wide-necked intracranial carotid artery (ICA) aneurysms from the petrous to superior hypophyseal segments, with later extension up to the terminus with small/medium aneurysms. Recently, the Surpass streamline flow-diverter (SSFD) has shown promise for diversifying flow-diversion options for aneurysm treatment. The SSFD differs from PED by increasing pore density while maintaining high metal-surface-area to ensure uniform flow disruption between the parent artery and aneurysmal lumen. The SSFD also expands from 5 mm up to 7 mm further diversifying treatment possibilities. There are few reports of flow-diverter stents used for cervical carotid pseudoaneurysms in the literature. However, the SSFD appears uniquely well adapted to targeting these aneurysms given the system's increased diameter/length options and expandability. Here, we describe our group's experience with the SSFD as a stand-alone flow-diversion solution for cervical carotid pseudoaneurysms. Materials and Methods: Data pertaining to cervical pseudoaneurysms treated with SSFD were gathered retrospectively January 2019 to now. Data included age, aneurysm type (sidewall, fusiform), size, symptoms, number of stents placed, and SSFD dimensions. Indications for stent placement included enlarging aneurysm, worsening compressive symptoms, and TIA/stroke. Complications were noted at four time points post-operatively: <24 hours, 30 days, 6 months and one year. Aneurysm occlusion degree was characterized using SMART grading (0 - arterial, coherent inflow jet to 4 - complete aneurysm occlusion) immediately post-procedure and at one-year follow-up angiogram. Six month post-procedure MRI/MRA was used for interval aneurysm occlusion assessment. Results: Three patients underwent SSFD placement for cervical carotid pseudoaneurysms. Ages ranged from 55–78. Two patients had symptomatic sidewall aneurysms measuring 1.7 × 2.1 cm and 1.8 × 1.3 cm. Both patients developed vocal hoarseness. One patient experienced vasovagal episodes while the other experienced TIAs. Another patient had an incidentally discovered fusiform aneurysm measuring 1.3 × 1.5 cm. There were no complications at any time point. One to three stents were deployed intra-operatively. Post-procedural SMART grade was 0 for two patients, and 2 for the third patient. One-year angiogram demonstrated SMART grade 3 occlusion with a minimally visualized neck remnant for one patient without parent artery stenosis. Six month MRI/MRA demonstrated total occlusion in another patient. Follow-up data was not available from the last patient as their initial intervention occurred <6 months ago. No stents migrated on follow-up imaging. The symptomatic patient had symptom resolution at one year. Conclusions: SSFD successfully treated three patients with cervical carotid pseudoaneurysms at our institution from 2019 to present with no complications, satisfactory angiographic appearance, and symptom resolution. Though further research is required to confirm these results, we demonstrate that SSFD appears both safe and effective for endovascular treatment of cervical carotid pseudoaneurysms. Disclosures: R. Achey: None. L. Sheikhi: None. T. Patterson: None. G. Toth: None. N. Zobenica Moore: None. M. Bain: None.